A new species of Smicromyrme from Israel (Hymenoptera: Mutillidae) - Pietro Lo Cascio; Flavia Grita (Fragmenta entomologica, 2014)
Smicromyrme bartolozzii sp. n. is described from a female specimen collected in a coastal desert of Israel. The new species is similar to S. ellipsifera (Gribodo, 1884), known for some localities of Eritrea, Ethiopia, Egypt and Djibouti. Sculpture of the pygidial plate, punctuation of the head and some morphological features of mesosoma are the main differential characters between both species.